Epidemiology of Orthopaedics Fractures in Under- Developed Country Due to Trauma, A Retrospective Study (Journal of Pakistan Orthopaedic Association, 2016)
Objective: To point out the factors leading to fractures, pattern of musculoskeletal fractures, keeping in view the age and sex of patients.Methods: In this study 740 patients admitted in orthopedic causality were included during July 2014 to December 2014.Their record was obtained from the admission files. Microsoft Excel was used to perform calculations and organize the data.Results: Out of 39 patients 31 were female and 8 were male with mean age of 55.58Â±8.35 and mean Body Mass Index of 29.21Â±4.80.Within 39 patients, 22 patients had left sided TKA and 17 patients had right sided TKA. The mean average of Knee and Function score was 95.38Â±1.23 and 94.17Â±9.87 respectively after 1 year follow up. Average knee range of motion had increased from 98.52Â±2.46 degrees preoperatively to 109.37Â±3.61 degrees postoperatively.Keywords: Open fracture, Road traffic accidents, fall, and Firearm injury.